Meta-Analysis Reveals Consistent Bacterial Responses to Land Use Change Across the Tropics - Petersen, Ian A. B.; Meyer, Kyle M.; Bohannan, Brendan J. M. (Frontiers in Ecology and Evolution, 2019)
Bacterial communities are a major component of global diversity and are intimately involved in most terrestrial biogeochemical processes. Despite their importance, we know far less about the response of bacteria to human-induced environmental change than we do about other organisms. Understanding the response of organisms to land use change is especially pressing for tropical rainforests, which are being altered at a higher rate than any other ecosystem. Here, we conduct a meta-analysis of studies performed in each of the major tropical rainforest regions to ask whether there are consistent responses of belowground bacterial communities to the conversion of tropical rainforest to agriculture. Remarkably, we find common responses despite wide variation across studies in the types of agriculture practiced and the research methodology used to study land use change. These responses include changes in the relative abundance of phyla, most notably decreases in Acidobacteria (-1.94±1.1 fold (average±95%CI)) and Proteobacteria (-1.38±1.0 fold) and increases in Actinobacteria (1.55±1.1 fold), Chloroflexi (3.47±1.2 fold) and Firmicutes (6.6±1.3 fold). We also find that alpha diversity (at the scale of single soil cores) consistently increases (1.17±1.0-fold) with ecosystem conversion. These consistent responses suggest that, while there is great diversity in agricultural practices across the tropics, common features such as the use of slash-and-burn tactics have the potential to alter bacterial community composition and diversity belowground.